The Andromeda strain - Crichton, Michael, 1942-2008 (Vintage Books, 2017)
"A military space probe, sent to collect extraterrestrial organisms from the upper atmosphere, is knocked out of orbit and falls to Earth. Twelve miles from the crash site, an inexplicable and deadly phenomenon terrorizes the residents of a sleepy desert town in Arizona, leaving only two survivors: an elderly addict and a newborn infant. The United States government is forced to mobilize Project Wildfire, a top-secret emergency response protocol. Four of the nation's most elite biophysicists are summoned to a clandestine underground laboratory located five stories beneath the desert and fitted with an automated atomic self-destruction mechanism for cases of irremediable contamination. Under conditions of total news blackout and the utmost urgency, the scientists race to understand and contain the crisis."--Page 4 of cover.